Comparative evaluation of DNA extraction kit, matrix sample and qPCR assays for bovine babesiosis monitoring - Okino, Cintia Hiromi; Giglioti, Rodrigo [UNESP]; Silva, Pamella Cristini; Oliveira, Henrique Nunes de [UNESP]; Sena Oliveira, Marcia Cristina de (Springer, 2018)
Bovine babesiosis caused by protozoan parasites Babesia bovis and B. bigemina is one of the most important causes of losses for the livestock industry in tropical and subtropical regions of the world. Therefore, highly sensitive and specific tools for these hemoparasites detection and monitoring are required, especially in carrier animals, in which low parasite levels were usually present. In this context, qPCR assays have been successfully and fairly used in last years. Aiming to improve the performance of Babesia levels monitoring by qPCR, some of main aspects of this methodology that may influence results were tested: DNA extraction kits, whole blood EDTA pre-treatment, blood source (tip of tail or jugular vein), erythrocytes isolation, FTA card interference and qPCR system of detection. Under our experimental conditions, both EDTA pre-treatment and FTA card application have no influence on the sensitivity of detection, and two DNA extraction kits provided higher sensitivity compared to others. As expected, blood samples collected from the tip of tail vessels presented higher levels of B. bovis DNA compared to those obtained from the jugular vein, and erythrocytes processed isolated has also improved the sensitivity compared to whole blood. Moreover, both qPCR assays here developed using hydrolysis probes for B. bovis and B. bigemina detection, presented enhanced reproducibility compared to qPCR assays using intercalating dye system. Even, qPCR for B. bigemina using hydrolysis probe here developed presented higher sensitivity compared to intercalating dye system. This study has contributed to the improvement of molecular diagnosis of bovine babesiosis, which may improve epidemiological studies related to these pathogens.
Keywords: qPCR; Matrix sample; DNA extraction; Hydrolysis probe; Intercalating dye; Bovine babesiosis